2022
DOI: 10.1044/2022_jslhr-21-00554
|View full text |Cite
|
Sign up to set email alerts
|

Structural Validity, Internal Consistency, and Rater Reliability of the Modified Barium Swallow Impairment Profile: Breaking Ground on a 52,726-Patient, Clinical Data Set

Abstract: Purpose: The purpose of this study was to extend the assessment of the psychometric properties of the Modified Barium Swallow Impairment Profile (MBSImP). Here, we re-examined structural validity and internal consistency using a large clinical-registry data set and formally examined rater reliability in a smaller data set. Method: This study consists of a retrospective structural validity and internal consistency analysis of MBSImP using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…From a voice standpoint, the reliability coefficients from the present study were within the range of those reported for auditory-perceptual assessments of voice, as previously outlined. Similarly, from a swallowing standpoint, the reliability coefficients in the present study are consistent with those frequently reported for visualperceptual assessments of swallowing, including measures related to pharyngeal residue [58][59][60][61], penetration/ aspiration [60][61][62][63][64], and swallowing physiology [65][66][67]. Lastly, while the reliability of acoustic and aerodynamic instrumental cough assessment measures is not routinely reported in research, current data demonstrate reliability coefficients range from 0.61 to 0.89 for non-automated measures (e.g., number of coughs, compression phase duration, peak flow rise time, inspiratory/expiratory volume) and 0.90-0.99 for automated measures (e.g., peak flow rate) [68][69][70][71][72][73][74][75][76][77].…”
Section: Discussionsupporting
confidence: 90%
“…From a voice standpoint, the reliability coefficients from the present study were within the range of those reported for auditory-perceptual assessments of voice, as previously outlined. Similarly, from a swallowing standpoint, the reliability coefficients in the present study are consistent with those frequently reported for visualperceptual assessments of swallowing, including measures related to pharyngeal residue [58][59][60][61], penetration/ aspiration [60][61][62][63][64], and swallowing physiology [65][66][67]. Lastly, while the reliability of acoustic and aerodynamic instrumental cough assessment measures is not routinely reported in research, current data demonstrate reliability coefficients range from 0.61 to 0.89 for non-automated measures (e.g., number of coughs, compression phase duration, peak flow rise time, inspiratory/expiratory volume) and 0.90-0.99 for automated measures (e.g., peak flow rate) [68][69][70][71][72][73][74][75][76][77].…”
Section: Discussionsupporting
confidence: 90%
“…Thus, it is crucial to consider the current state of VFSS‐based research focused on normal UES function. A lack of well‐tested and validated swallow task procedures, such as the Modified Barium Swallow Impairment Profile (MBSImP) protocol, have been applied to test normal UES function 34–37 . Studies have explored an array of contextual factors on UESOdur and UESmax, including age, 19,20,23–25,28–30,32 sex, 19,20,23–26,30,31,33 viscosity, 19–21,30,31 and volume, 19,22,25–27,29,31–33 but we are unaware of a single, large‐scale study that has investigated the collective interaction of all these factors using a wide range of standardized swallow tasks that have been well‐tested to identify swallowing impairment accurately.…”
Section: Introductionmentioning
confidence: 99%
“…A lack of well-tested and validated swallow task procedures, such as the Modified Barium Swallow Impairment Profile (MBSImP) protocol, have been applied to test normal UES function. [34][35][36][37] Studies have explored an array of contextual factors on UESOdur and UESmax, including age, 19,20,[23][24][25][28][29][30]32 sex, 19,20,[23][24][25][26]30,31,33 viscosity, [19][20][21]30,31 and volume, 19,22,[25][26][27]29,[31][32][33] but we are unaware of a single, large-scale study that has investigated the collective interaction of all these factors using a wide range of standardized swallow tasks that have been well-tested to identify swallowing impairment accurately. These current research gaps limit the overall context in which these measures can be interpreted clinically.…”
Section: Introductionmentioning
confidence: 99%